Country of origin of a product: Country of Brand or Country of Manufacture? A study on Italian smartphone consumers - Grifo, Vincenzo (2016)
For years, the negative country image associated with Chinese manufactures has hindered the perception and acceptance of Chinese products in developed markets, such as Italy. As more Chinese multinational companies are rising on the global stage as important players, current consumers’ perception of China’s country image is among the most relevant topics for research. Nonetheless, in the era of globalisation where companies manufacture and source globally, products with multiple countries of origin, such as smartphones, have paved the way to a reconceptualisation of the way consumers perceive products’ country of origin, by distinguishing the country of origin of the brand from the country of manufacture. Accordingly, the aim of this dissertation is to assess the extent by which the relationship between country of brand and country of manufacture information cues influences Italian consumers’ purchasing intention towards Chinese smartphones. Based on data collected from three survey experiments, conducted on a total of 366 Italian consumers, the findings underline that consumers give more importance to the fact that a product’s brand originates from a country with a positive country image, rather than where the product itself is actually manufactured. The main conclusion to be drawn from this empirical study is that Chinese smartphones still suffer from a negative country image, which could be somewhat mitigated by the acquisition of foreign brands and commercialisation of the products under those brands.